Composite trade shares measurement for trade openness on inflation among selected developing countries - Tee, Heng Guan; Kaliappan, Shivee Ranjanee; Lee, Chin; Said, Rusmawati (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
This paper examines the nexus between trade openness and inflation among 42 selected developing countries between 1985 and 2014 using five years averages to validate the Romer hypothesis for the role played by trade openness in influencing inflation. As suggested by Romer hypothesis, trade openness has negative relationship with inflation yet there is no empirical consensus between trade openness and inflation. This paper follows the newly developed measurement proposed by Squalli and Wilson (2011) to consider a multidimensional index, composite trade shares, to measure for trade openness. The results from system GMM estimation indicated the rejection of Romer hypothesis when using Composite trade shares measurement for trade openness but support Romer hypothesis when using the trade shares measurement. The rejection of Romer’s hypothesis using the composite trade shares measurement suggests that policymakers need to aware of inflation following greater trade openness. Apart from that, income redistribution and greater government expenditures are important in reducing the negative impact brought by greater trade openness.